2022
DOI: 10.3390/jcm11216428
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Vitreoretinal Surgery

Abstract: Advances in vitreoretinal surgery provide greater safety, efficacy, and reliability in the management of the several vitreoretinal diseases that benefit from surgical treatment. The advances are divided into the following topics: scleral buckling using chandelier illumination guided by non-contact visualization systems; sclerotomy/valved trocar diameters; posterior vitrectomy systems and ergonomic vitrectomy probes; chromovitrectomy; vitreous substitutes; intraoperative visualization systems including three-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 86 publications
0
10
0
2
Order By: Relevance
“…Numerous vitreoretinal diseases can lead to the substitution of the vitreous body with another solution, a process known as vitrectomy, as part of the medical treatment. [180] The physiological vitreous is mainly composed of water, representing 98% of its composition, as well as collagen, and glycosaminoglycans (i.e. HA, chondroitin sulfate, and heparan sulfate).…”
Section: Hydrogel-based Vitreous Substitutesmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous vitreoretinal diseases can lead to the substitution of the vitreous body with another solution, a process known as vitrectomy, as part of the medical treatment. [180] The physiological vitreous is mainly composed of water, representing 98% of its composition, as well as collagen, and glycosaminoglycans (i.e. HA, chondroitin sulfate, and heparan sulfate).…”
Section: Hydrogel-based Vitreous Substitutesmentioning
confidence: 99%
“…The vitreous body is a transparent gel‐like structure that has tremendous importance in biochemical and physiological functions, as well as in the optical properties of the eye. Numerous vitreoretinal diseases can lead to the substitution of the vitreous body with another solution, a process known as vitrectomy, as part of the medical treatment [180] . The physiological vitreous is mainly composed of water, representing 98% of its composition, as well as collagen, and glycosaminoglycans ( i.e.…”
Section: Ophthalmic Applications Of Hydrogelsmentioning
confidence: 99%
“…These factors were all identified by forward and backward stepwise selection methods in a Cox regression model. Previous studies have indicated that preoperative PVR is a significant predictor and risk factor for postoperative PVR [6,12,[19][20] . For RD patients with preoperative PVR, the incidences of postoperative PVR and recurrent RD were reported to be significantly increased [21][22] .…”
Section: Internal and External Validation Of The Nomogrammentioning
confidence: 99%
“…The incidence of postoperative PVR ranged from 4% to 34% in prospective studies [5] . Reduction of the incidence of PVR by surgical techniques or agents has always been a challenge for vitreoretinal surgeons [6] . A key step in achieving this is to identify patients at high risk for PVR development because they would benefit the most.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Vitreoretinal cerrahi cihazlardaki en son gelişmeler arasında 23, 25 ve 27 gauge vitrektomi probları, yeni kesici tasarımlar, daha yüksek kesim hızı, geliştirilmiş göz içi basınç kontrolü, yeni endoillüminasyon, diatermi teknolojileri ve birleşik ön/arka segment cerrahi yetenekler bulunmaktadır. 3,4 Bu yazıda ön ve arka segment cerrahi işlemlerinde kullanılan Optikon 2000 S.p.A. (ASSISTANT) vitrektomi sisteminin özellikleri ve çalışma prensipleri tanıtılacaktır (Şekil 1).…”
Section: Opticon Vitrectomy System Girişunclassified